2022
DOI: 10.1002/ceat.202200097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transmembrane Pressure on Antifouling Properties of PVC/Clinoptilolite Ultrafiltration Nanocomposite Membranes

Abstract: Novel polyvinyl chloride (PVC)/clinoptilolite nanocomposite membranes for water treatment were fabricated by non‐solvent‐induced phase separation and characterized with respect to their hydrophilicity, porosity, surface roughness, thermal stability, and surface and cross‐sectional morphology. All prepared membranes were evaluated in a submerged system for the removal of humic acid (HA) under various vacuum transmembrane pressure (TMP) conditions. The hydrophilicity, porosity, and thermal stability of the membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…When Figure 2 are examined in detail, it is seen that the 5 wt.% additive has a more homogeneous distribution within the fiber structure. This result can be interpreted as the distribution of CLN particles contributes to both the increase in the hard segment structure of the fibers and the formation of hydroxyl groups between the fibers 57 . This interpretation is also in agreement with the results obtained from FTIR data (Table S1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…When Figure 2 are examined in detail, it is seen that the 5 wt.% additive has a more homogeneous distribution within the fiber structure. This result can be interpreted as the distribution of CLN particles contributes to both the increase in the hard segment structure of the fibers and the formation of hydroxyl groups between the fibers 57 . This interpretation is also in agreement with the results obtained from FTIR data (Table S1).…”
Section: Resultssupporting
confidence: 91%
“…This result can be interpreted as the distribution of CLN particles contributes to both the increase in the hard segment structure of the fibers and the formation of hydroxyl groups between the fibers. 57 This interpretation is also in agreement with the results obtained from FTIR data (Table S1). However, it was found that agglomeration occurred at 10 wt.% CLN concentration.…”
Section: Morphological Analysis Of Cln/tpu Nanofibrous Scaffoldssupporting
confidence: 91%
“…The incorporation of clinoptilolite in the nanocomposite membrane led to higher hydrophilicity owing to the presence of hydroxyl groups and higher water flux (13.9 → 20.2 ) after 300 min at 0.1 bar pressure, but resulted in a decrease in mechanical strength. The antifouling performance was improved, with a decrease in irreversible fouling rate (19.3 → 6%) and an increase of FRR (80.7 → 94%) for a 0.5 wt.% PVC/clinoptilolite nanocomposite compared to the pristine polymer [ 273 ]. Casadellà et al prepared MMMs by blending different wt.% of clinoptilolite into PSf and PVP matrix for selective recovery of and .…”
Section: Incorporation Of Nps In Tfncs/mmmsmentioning
confidence: 99%
“…UF membranes with high water flux in low trans-membrane pressure can achieve the proper rejection of substances such as colloids, proteins and natural organic matters (NOMs). 4 Among different polymers which are used for UF membranes, PVC is an outstanding material due to robust mechanical strength, low cost, good thermal stability, and other excellent properties such as high resistance to acids, bases, and solvents. 5 These great properties make PVC as an interesting choice for UF processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, UF membrane process receives a wider attention due to its intermediate performance to MF and NF/RO membranes. UF membranes with high water flux in low trans‐membrane pressure can achieve the proper rejection of substances such as colloids, proteins and natural organic matters (NOMs) 4 …”
Section: Introductionmentioning
confidence: 99%